2018
DOI: 10.23956/ijermt.v6i11.54
|View full text |Cite
|
Sign up to set email alerts
|

Developing Sustainable Marketing Strategy for Electric Vehicle (EV) - Automotif

Abstract: Abstract:uture of urban mobility is electric vehicle (EV) and there is no doubt about it. At the same time, it is considered as a new product among the automobile industry. However, entire EV industry is evolving and lot of R&D is going to get major lead in this industry. This project puts forward and determines sustainable business strategy for EV by doing external environment analysis using PESTEL and Porter's five forces and mapping of opportunities and threat which effects company's direction as well as to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Table III summarizes that competitive strategies have been discussed from the works of other scholars in relation to automotive industry. Authors found that NPD is still the area of interest for those scholars such as the diversity of power trains and increasing product variants (Diffner et al, 2018), fostering NPD (Kotturu and Mahanty, 2017), continuously develop product (Pahurkar and Metha, 2017) and process development (Holtskog, 2017). The research on supplier as competitive strategies has been discussed by Kotturu and Mahanty (2017), Manello and Calabrese (2018) and Karayel (2017) related to transfer responsibilities to component suppliers, suppliers' technology, product diversification and knowledge.…”
Section: Discussion and Practical Implications Of The Review Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Table III summarizes that competitive strategies have been discussed from the works of other scholars in relation to automotive industry. Authors found that NPD is still the area of interest for those scholars such as the diversity of power trains and increasing product variants (Diffner et al, 2018), fostering NPD (Kotturu and Mahanty, 2017), continuously develop product (Pahurkar and Metha, 2017) and process development (Holtskog, 2017). The research on supplier as competitive strategies has been discussed by Kotturu and Mahanty (2017), Manello and Calabrese (2018) and Karayel (2017) related to transfer responsibilities to component suppliers, suppliers' technology, product diversification and knowledge.…”
Section: Discussion and Practical Implications Of The Review Studymentioning
confidence: 99%
“…Hyundai's product development tries to adjust to local needs (Chen, 2017), and Tesla promotes the development of the new energy vehicle industry innovation environment (Liu and Meng, 2017). Other scholars stated that competitive strategies by increasing product variants (Diffner et al, 2018), fostering NPD (Kotturu and Mahanty, 2017), continuously develop product (Pahurkar and Metha, 2017) and process development (Holtskog, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…al. ( 2017 ) Internationalization Sushil and Garg ( 2019 ) Policymaking toward EV Pahurkar and Metha ( 2017 ) Performance Market share gain, customer satisfaction, better capacity utilization, and high productivity Alagappan et. al.…”
Section: Literature and Conceptual Backgroundmentioning
confidence: 99%